Национальные экономики и национальные промышленные системы в современном мире: введение в проблему - Вишневская, Е.Н. (Економіка промисловості, 2014)
Рассмотрено понятие национальной экономики, которую предложено понимать как эволюционирующий организм, имеющий свою историю и характеризующийся уникальным сочетанием движущих сил развития в пространстве и времени. Обосновано, что национальные экономики и промышленные системы сгруппированы в экономические популяции, формирующиеся под влиянием географических, социобиологических, языковых, религиозных, культурных и иных факторов. Розглянуто поняття національної економіки, яку запропоновано розуміти як організм, що еволюціонує, має свою історію і характеризується унікальним поєднанням рушійних сил розвитку у просторі і часі. Обґрунтовано, що національні економіки й індустріальні системи згруповані в економічні популяції, які формуються під впливом географічних, соціобіологічних, мовних, релігійних, культурних та інших факторів. The concept of national economy is proposed. It is offered to understand it not as the mechanical set of economic units, but as the evolving organism that has its own history and is characterized by a unique combination of driving forces of development in space and time. It is proved that each national economy represents something special, variant from other economies not only in quantitative aspect (according to numerical characteristics of constituent elements - the population, wealth, income, etc.), but first of all in qualitative aspect formed in space and time under the influence of geographical, socio-biological, language, religious, cultural, and other factors. All successful national economies in the modern world are externally very similar: they are the mixed units with a certain combination of the state and market, possessing the multilevel monetary, tax and budgetary systems, developed markets of factorsof production, modern industry, infrastructure, etc. However, from the substantial point of view those national economies which have risen quickly in the last decades build their systems of the social and economic relations in a different way than the western democracies. It is visible first of all from geographically and historically caused socio-cultural norms which are the cornerstone of economic transaction and mechanisms of administrative decisions making. It is proved that national economies are grouped in the economic populations which are forming under the influence of geographical, sociobiological, language, religious, cultural and other factors. This approach, based on evolutionary methodology, is characterized as a methodological populationism.The traditional typology of national economies also has important analytical value. In the last decades, for example, the concept of a variety of capitalisms has gained popularity in the world, according to which it suggests to distinguish on the basis of on one or several signs, for example, Anglo-Saxon, European-continental, Social-democratic, and Asian capitalisms. Such analysis really allows revealing important typical features of certain national economies which are the representatives of different populations. But, in principle, their direct comparison is insufficiently correct and constructive as it is more correct and constructive to compare not the separate social organisms relating to different populations but the organisms of one population or different populations among themselves.